Executive Characteristics as Moderators: Accounting Conservatism and Tax Avoidance in Consumer Sectors - Siahaan, Magda (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study aims to determine the effect of accounting conservatism, sales growth, audit committees, and executive characteristics on tax avoidance practices, especially the moderating role of executive characteristics to support the formulation of more effective and fair tax policies. Sample data from the cyclical and non-cyclical consumer sectors in Indonesia, analyzed using STATA – Statistics and Data 17, found that accounting conservatism, sales growth, and audit committee significantly positively affect tax avoidance. In contrast, executive characteristics have a significant positive effect, while executive characteristics also significantly weaken the effect of accounting conservatism and sales growth on tax avoidance but do not moderate the effect of the audit committee. The moderating role of executive characteristics in influencing the relationship between accounting conservatism, sales growth, and audit committees on tax avoidance practices is rarely studied so that it can provide good implications for consumer sector companies.